1389 Axillary Staging in Ductal Carcinoma in Situ with Microinvasion: A Systematic Review. (12th October 2021) - Choi, B; Jegatheeswaran, L; Patel, V; Lupi, M; Babu, E; Nakhoul, M; Haria, P l
Abstract: Introduction: Ductal carcinoma in situ with microinvasion (DCISM) is a rare subtype of DCIS, with a foci of tumour cells penetrating through the basement membrane. A conundrum for surgeons is that definitive diagnosis is made upon histological examination of the final specimen. In the UK, there are no specific guidelines on the role of axillary staging in the management of DCISM cases. Method: A systematic review was conducted on the databases MEDLINE and Embase using the keywords: breast, DCISM, microinvasion, "ductal carcinoma in situ with microinvasion", sentinel lymph node biopsy, SLNB, axillary staging was performed. 23 studies were selected for analysis. Primary outcome was the positivity of lymph node metastases; secondary outcome looked at characteristics of DCISM that may affect node positivity. Results: 2959 patients were included. Significant heterogeneity was observed amongst the studies with regards to metastases (I 2 =61%; P < 0.01). Lymph node macrometastases was estimated to be 2%. Significant subgroup difference was not observed between SLNB technique and lymph node macrometastases (Q = 0.74; p = 0.69). Statistical significance was observed between the focality of the DCISM and lymph node macrometastases (Q = 8.71; p = 0.033). Conclusions: DCISM is not linked with higher rates of clinically significant metastasis to axillary lymph nodes. Survival rates are very similar to those seen in cases of DCIS. Current evidence suggests that axillary staging in cases of DCISM will not change their overall management. A conscientious multidisciplinary team approach evaluating pre-operative clinical and histological information to tailor the management specific to individual cases of DCISM would be a preferred approach than routine axillary staging.